Introductory soil science : - Troeh, Frederick R. (Iowa State Univ., 1995)
Understanding soils and their relationship to the environment is increasing in importance as we learn more about the environment in which we live. Soils are important in crop production, in serving as a buffer in the environment, as a building medium, and in a multitude of other applications. In the third edition of this manual, new materials addressing specific environmental concerns related to crop production and groundwater supplement the exercises from previous editions. Flexibility in the exercises allows the instructor and students to tailor applications to local resources and conditions. The materials included give substantial meaning to otherwise abstract topics such as soil profiles and horizons, soil texture, cation exchange capacity, nitrate leaching, and non-point source pollution. Students will gain an understanding of how much water a soil can hold, how rapidly soluble materials such as nitrates may leach through a given soil, how much lime a soil may need, and how much soil loss can be tolerated. These exercises provide a basic understanding of soils and serve as background material for students who will take advanced courses in soils. This text is an ideal supplement to regular class work in an introductory soils course.